2013
DOI: 10.1021/jf402821r
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Amylose and Tea Polyphenols Modulates the Postprandial Glycemic Response to High-Amylose Maize Starch

Abstract: High-amylose maize starch (HAM) is a common source material to make resistant starch with its high content of amylose (>70%). In the current investigation, the self-assembly of amylose in the presence of bioactive tea polyphenols (TPLs) and resulting slow digestion property of starch were explored. The experimental results using a mouse model showed a slow digestion property can be achieved with an extended and moderate glycemic response to HAM starch cocooked with TPLs. Further studies using a dilute aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(120 citation statements)
references
References 32 publications
1
119
0
Order By: Relevance
“…Results show that the mentioned interactions decreased the solubility of derivatives and modified the hydrophobic-hydrophilic character of the studied proteins. 19,23,24 The affinity of polyphenols to polysaccharides strongly depends on the molecular size, conformational mobility and shape as well as solubility of polyphenols. Moreover, changes in the mentioned physicochemical properties adversely affected the digestibility of the derivatized proteins in the model involving the action of the selected enzymes (trypsin, chymotrypsin, pepsin and pancreatin).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that the mentioned interactions decreased the solubility of derivatives and modified the hydrophobic-hydrophilic character of the studied proteins. 19,23,24 The affinity of polyphenols to polysaccharides strongly depends on the molecular size, conformational mobility and shape as well as solubility of polyphenols. Moreover, changes in the mentioned physicochemical properties adversely affected the digestibility of the derivatized proteins in the model involving the action of the selected enzymes (trypsin, chymotrypsin, pepsin and pancreatin).…”
Section: Resultsmentioning
confidence: 99%
“…12,14,[20][21][22] Additionally, binding of phenolics to proteins negatively affects its biological activity by the formation of indigestible complexes or chemical modification of amino acids. 22 On the other hand, studies by Chai et al 23 and Barros et al 24 demonstrate that the hydrogen or hydrophobic interactions of phenolics may decrease starch digestibility by the modification of its physicochemical properties (e.g. 22 On the other hand, studies by Chai et al 23 and Barros et al 24 demonstrate that the hydrogen or hydrophobic interactions of phenolics may decrease starch digestibility by the modification of its physicochemical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The carboxyl groups in the fatty acids could facilitate the association of the amylose chains through hydrogen bonding. Chai et al reported the presence of hydrogen bonds between amylose chains and tea polyphenols (TPLs) (Chai, Wang, & Zhang, 2013). The authors showed that the TPL molecules used hydrogen bonding to bridge the amylose chains and form B-type crystals.…”
Section: Effect Of the Bi-functional Carboxyl Group In The Fatty Acidmentioning
confidence: 99%
“…Similar to previous studies (Barros, Awika, & Rooney, 2012;Deshpande & Salunkhe, 1982), tea polyphenols investigated in this study could bind with maize starch granules to different degrees. The forces that drive the interactions are proposed to be hydrophobic force and hydrogen bonding (Barros, Awika, & Rooney, 2012;Chai, Wang, & Zhang, 2013). The binding of PPA with starch increased with the starch concentration increasing in both the absence and presence of tea polyphenols, because the starch granules act as an adsorbate in the suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have also been reported to interact directly with starch through hydrophobic forces and hydrogen bonding (Zhu, Cai, Sun, & Corke, 2009), and thus influencing the exposure of hydrolysis sites on starch and reducing starch digestibility (Chai, Wang, & Zhang, 2013). In addition, polyphenols that are adsorbed onto granular starch may also have inhibitory activity against α-amylase (Yang, He, & Lu, 2014).…”
Section: Introductionmentioning
confidence: 99%